2021
DOI: 10.1111/ajd.13762
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical, pathological and genetic characteristics of epidermolysis bullosa in New Zealand

Abstract: Objective: To establish the epidemiological, clinical, pathological and genetic characteristics of epidermolysis bullosa (EB) in New Zealand (NZ).Methods: Participants were recruited through the Dystrophic Epidermolysis Bullosa Research Association of New Zealand (DEBRA NZ). Dedicated EB nurse medical records, Genetic Health Service NZ (GHSNZ) records and, where available, public hospital records were manually reviewed for relevant clinical data.Results: Ninety-two participants took part in the study (56% part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…EB is considered a rare or orphan disease 5 . Various EB prevalence and incidence rates have been reported across countries worldwide 10–16 . Collected epidemiological data were acquired from a 16‐year prospective cross‐sectional, longitudinal study conducted on 3271 patients of all ages in the United States enrolled in the National EB Registry (NEBR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EB is considered a rare or orphan disease 5 . Various EB prevalence and incidence rates have been reported across countries worldwide 10–16 . Collected epidemiological data were acquired from a 16‐year prospective cross‐sectional, longitudinal study conducted on 3271 patients of all ages in the United States enrolled in the National EB Registry (NEBR).…”
Section: Introductionmentioning
confidence: 99%
“…5 Various EB prevalence and incidence rates have been reported across countries worldwide. [10][11][12][13][14][15][16] Collected epidemiological data were acquired from a 16-year prospective cross-sectional, longitudinal study conducted on 3271 patients of all ages in the United States enrolled in the National EB Registry (NEBR). The overall prevalence and incidence of hereditary EB during this period were 11.1 and 19.6 per 1 million population and per 1 million live births, respectively.…”
mentioning
confidence: 99%
“…1,3,4 Heterogenous EB prevalence rates have been reported across countries worldwide, with values ranging from 4.0 to 54.0/million population, reflecting variabilities in populations and data sources. [5][6][7] In France, no epidemiological data have been published, but data on EB patients collected through the network of national and local rare disease centres were available from the French national registry for rare diseases (BNDMR). 8 A retrospective analysis has been performed using BNDMR data from EB patients registered between January 2007 and December 2021.…”
mentioning
confidence: 99%
“…Nevertheless, the French prevalence rates by EB type were within the range of those in other countries. [5][6][7] As regards visits to expert centres, the annual visit frequency per patient was in accordance with the national recommendation 9 of a minimum of one visit/year, for each EB type (Table 1). DEB and JEB patients had the highest frequencies.…”
mentioning
confidence: 99%
“…Former epidemiological studies on EB showed considerably varying figures, partly reflecting the challenge of epidemiological studies of EB, and rare diseases in general. The reported prevalences and incidences (per million) were, respectively, 22·4 and 41·3 in the Netherlands and 11·1 and 19·6 in the USA; prevalences (per million) were 10·3 in Australia, 19·5 in New Zealand, 6·7 in Iran and approximately 20 in Slovenia 4–9 . These varying figures can be explained by factors influencing case ascertainment, like demographic factors (country size, and number and distribution of EB centres) and factors related to healthcare systems (insurance aspects, diagnostic possibilities, awareness among non‐EB specialists about the disease, and centres of expertise).…”
mentioning
confidence: 99%